A new species of Paratrigonidium Brunner von Wattenwyl, 1893 from Hainan, China (Orthoptera: Trigonidiidae; Trigonidiinae) - He, Zhuqing; Liu, Yuqing; Lu, Hui; Wang, Hanqiang; Wang, Peng; Li, Kai (Zootaxa, 2017)
One new species, Paratrigonidium chloropodum sp. nov., is described from Hainan, China. The type specimens are deposited in East China Normal University, Biology of History Museum (ECNU). S. venustula is moved to genus Paratrigonidium as P. venustulum comb. nov. P. vittatum Brunner von Wattenwyl, 1893 syn. is the junior synonym of P. venustulum.